The effects of student- and teacher-led tootling on student disruptive behavior - Thoele, Jillian M.; Sayeski, Kristin L. (Frontiers in Education, 2024)
The foundation of effective management lies in the recognition and reinforcement of appropriate behaviors. Researchers have found that class-wide, group-contingency-based classroom management approaches can be an efficient and effective way to promote desired student behavior. For this study, we examined the effect of Tootling, a peer-mediated, group-contingency approach wherein students identify and report on their peers’ prosocial behaviors. We used an alternating treatment single-case research design to evaluate and compare the impact of student- and teacher-led Tootling on disruptive behavior and academic engagement for five elementary students. Student-led Tootling, teacher-led Tootling, and no-Tootling conditions were alternated daily following a systematically blocked, randomized schedule. After each series of the three conditions, a group-based concurrent chain preference assessment was conducted to determine students’ choice of condition. Disruptive behavior decreased for all five students during both student- and teacher-led conditions, and although data were variable, all five students increased academic engagement during student-led Tootling. Findings from the concurrent chain preference assessment revealed most students preferred the student-led Tootling condition. Social validity questionnaires indicated teachers preferred student-led Tootling and found it acceptable and feasible, and student questionnaires indicated they wanted to continue using Tootling in their classrooms. Maintenance data demonstrated all three teachers continued implementing student-led Tootling after the study’s completion. Implications and recommendations for future research are discussed.